Generation Y – die „neuen" Väter?: Empirische Analyse für Personalverantwortliche - Schmidt, Cynthia (Tectum Verlag, 2023)
Generation Y is not exactly revolutionising the labour market with the best reputation. This generation does not submit to office slavery and is not prepared to make concessions with regard to the compatibility of family and career. A new species of fathers also seems to have developed among this generation. The new father no longer wants to be just the breadwinner. He sees himself as a participating father, wants an emotional bond with his child and no longer just to spend quality time with his child on Sundays. The desire is great, but it is clear that the implementation is clearly lacking. Obstacles and necessary adjustments can be found not least among mothers, politicians and employers.